BRAZILIAN AGRO-INDUSTRIAL SECTOR AND THE MODERNIZATION OF THE ECONOMY - de Oliveira, Milena dos Sandos; Cavichioli, Fábio Alexandre (Revista Interface Tecnológica, 2023)
On the world stage, interest in issues of environmental impact and the advancement of agribusiness is growing. There is an emphasis on the issue of agribusiness versus the environment. The quest to combine the increase in agribusiness without impacting the environment so much is also a concern for planet Earth as well. In this way, due to the importance of debating these issues and creating new methods of rapid implementation, in order to have strategies that the agro continues to advance without deteriorating the land and the environment, this article will discuss the subject, better strategies and better communication of these new initiatives by companies and this new movement of agroecology. Objetive is a review bibliographical on the subject based on the scientific literature. This article sought to bring, initially, a historical context and the various types of existing agriculture, focusing on the firmness of agribusiness and its agricultural power and on the modeling of agroecology as a social, political and science practice, thus bringing out how important it is to scientific communication and society, mainly from the countryside and their experiences for a better regulation of the techniques used allied to biotechnology in agriculture, mainly the issue of pesticides and even genetic modifications.
Keywords: Agribusiness; Agroecology; Agricultural sector innovations